DETERMINAN KINERJA SISTEM INFORMASI AKUNTANSI DENGAN MODERASI KOMPLEKSITAS TUGAS - Nisa Kamela, 10.05.52.0009; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
This study aims to analyze the factors that affect the performance of accounting information systems with variable user participation information systems, the ability of users of information systems, training and user education information systems moderated by task complexity. The population and the sample is PD BPR BKK in Central Java and Yogyakarta. The number of BPR available in Central Java and Yogyakarta in 1242 covers much of central and branch offices. Sampling technique used was accidental sampling. Data retrieval techniques by means of a questionnaire spread. The analysis technique used is multiple linear regression analysis and to examine the effect of moderating variables used models of the absolute value of the difference between the independent variables. These results indicate that user participation information systems significant positive effect on the performance of SIA. The ability of information systems users significant negative effect on the performance of SIA. Training and user education system not significant negative effect on the performance of SIA. Participation information system users significant positive effect on the performance of SIA with moderation task complexity. The ability of users of information systems is not significant positive effect on the performance of SIA with moderation task complexity. Training and user education system not significant negative effect on the performance of SIA with moderation task complexity.Keywords: information system user participation, the ability of users of information systems, training and user education information system, the complexity of the taskÂ